Changes in the human plasma and urinary metabolome associated with acute dietary exposure to sucrose and the identification of potential biomarkers of sucrose intake. Issue 2 (15th September 2015) - Beckmann, Manfred; Joosen, Annemiek M.; Clarke, Michelle M.; Mugridge, Owen; Frost, Gary; Engel, Barbara; Taillart, Kathleen; Lloyd, Amanda J.; Draper, John; Lodge, John K.
Abstract : Scope: The intake of sucrose is of public health concern but limited information is available on the metabolic effects of short‐term exposure. Our aim was to use metabolomics to investigate the metabolic impact of acute sucrose exposure. Methods and results: We performed a randomized, parallel, single‐dose feeding study on healthy females ( n = 90, aged 29.9 ± 4.7 years, BMI 23.3 ± 2.5 kg/m 2 ) consuming either 0, 50, or 100 g sucrose in 500 mL water. Blood and urine samples were taken before and 24 h post sucrose intake. Urine and plasma samples underwent detailed metabolite profiling analysis using established protocols. Flow‐injection electrospray MS fingerprinting analysis showed that 3 h after intake was the most informative time point in urine and plasma and out of 120 explanatory signals, highlighted 16 major metabolite signals in urine and 25 metabolite signals in plasma that were discriminatory and correlated with sucrose intake over time. The main confirmed metabolites positively correlated with intake were sucrose, fructose, and erythronic acid, while those negatively correlating with intake included fatty acids and derivatives, acyl‐carnitines, and ketone bodies. GC‐TOF‐MS profiling analysis confirmed the fingerprinting data. Conclusion: Acute exposure to sucrose identified a number of metabolites correlated with sucrose intake and several compounds attributed to metabolic fasting.